The Nature of Magmatism in the Appalachian Orogen 1997
DOI: 10.1130/0-8137-1191-6.235
|View full text |Cite
|
Sign up to set email alerts
|

Low-potassium, trondhjemitic to granodioritic plutonism in the eastern Blue Ridge, southwestern North Carolina-northeastern Georgia

Abstract: Plutons and dikes of the eastern Blue Ridge, North Carolina and northeasternGeorgia, were emplaced syntectonically ca. 400 Ma in the evolving southern Appalachian orogen. These intrusive rocks are uniformly felsic and peraluminous, ranging continuously from trondhjemitic to granodioritic in composition with no associated mafic or intermediate rocks. The trondhjemites are very low in K and in incompatible and high field strength trace elements; are rich in Al, Na, and Sr; and have low 87 Sr/ 86 Sr and δ 18 O an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…of Rahu are due to contamination of Separation Point magmas with Paleozoic continental crust (e.g., Waight et al, 1998). A similar model has been proposed by Miller et al (1997) for trondhjemitic to granodioritic plutonism in the southern Appalachians. Figure 9.…”
Section: Crustal Assimilation In Inboard Plutonssupporting
confidence: 61%
“…of Rahu are due to contamination of Separation Point magmas with Paleozoic continental crust (e.g., Waight et al, 1998). A similar model has been proposed by Miller et al (1997) for trondhjemitic to granodioritic plutonism in the southern Appalachians. Figure 9.…”
Section: Crustal Assimilation In Inboard Plutonssupporting
confidence: 61%
“…Importantly, these two overlapping belts occur within the eastern Blue Ridge and are not separated by major faults (e.g., Brevard fault zone), as observed in Georgia and North Carolina, thereby limiting uncertainties associated with younger fault displacements. Geochemical models for the trondhjemite and granodiorite magmas in the eastern Blue Ridge of Georgia and North Carolina are consistent with intracrustal partial melting involving amphibole and biotite dehydration reactions, leaving behind a plagioclase-poor, garnet-bearing residue at deep-crustal levels (>30 km depth; Miller et al, 1997). Highly variable and negative zircon Hf isotope data from the Alabama plutons support an intracrustal melting origin; however, some weakly positive ε Hf(i) values are compatible with contributions from a mantle source.…”
Section: Timing and Significance Of Paired Magmatic Belt Constructionmentioning
confidence: 79%
“…The parent rock to unaker might appear to be a coarse-grained granite or feldsparbearing pegmatite. Ramsay et al (2001) have demonstrated that the parental rocks for this primary clay assemblage are a suite of essentially northeast-trending pegmatite intrusions and quartz veins that were syntectonically emplaced during the Acadian Orogeny (Miller et al, 1997). Again, the description suggests that both Heylyn and Frye had firsthand experience of this material and were not hastily filing a patent to stop other competitors, such as Andrew Duché (Watney, 1973:10) from obtaining exclusive rights.…”
Section: Signedmentioning
confidence: 99%